Preparation of TiO2Â¬ Bamboo Leaves Ash Composite as Photocatalyst for Dye Photodegradation - Prihatiningsih, Prihatiningsih; Pertiwi, Lita Dewi; Fatimah, Is (Chemistry Department, Universitas Islam Indonesia, 2017)
Textile waste containing dye can generate environmental problems especially for human. Therefore some techniques are developed to overcome the impact of toxic contaminant from dyes residue, one of these is the photocatalysis technique. The photocatalysis mechanism TiO2 is a popular photocatalyst and in order to improve its activity the composite formation with a some solid support are attempted. The development of TiO2 composite with a sustainable support source; bamboo leaves was conducted. The composite was prepared by dispersing titanium isopropoxide into bamboo leaves ash (BLA) followed by calcination process. Hysicochemical characterization of the photocatalyst was performed by using XRD, gas sorption analyzer and SEM-EDX analysis. By the characterization it is found that BLA contains silica in highest percentage and furthermore TiO2 in the mixed anatase and rutile phases were formed the composite.